2019
DOI: 10.1002/mds.27814
|View full text |Cite
|
Sign up to set email alerts
|

Morphological MRI investigations of the hypothalamus in 232 individuals with Parkinson's disease

Abstract: Background The pathophysiology of the hypothalamic involvement in Parkinson's disease (PD) is not well understood. The objective of this study was the quantification of hypothalamic volumes in vivo in PD. Methods High‐resolution T1‐weighted magnetic resonance imaging (MRI) data from 232 individuals with PD and 130 healthy non‐PD individuals were used for quantification of the hypothalamic volumes. Results The hypothalamus in PD was not atrophied, as indicated by volumetric analyses in the prospectively collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…All reported volumes were normalized for TIV, age, and sex using a linear regression model. 8,23 Group differences in demographic and clinical characteristics as well as normalized hypothalamic volumes were analyzed using independent twosample t test for continuous variables and χ 2 test for dichotomous variables. Mann-Whitney U test was performed instead if the dataset failed to pass the Kolmogorov-Smirnov normality test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All reported volumes were normalized for TIV, age, and sex using a linear regression model. 8,23 Group differences in demographic and clinical characteristics as well as normalized hypothalamic volumes were analyzed using independent twosample t test for continuous variables and χ 2 test for dichotomous variables. Mann-Whitney U test was performed instead if the dataset failed to pass the Kolmogorov-Smirnov normality test.…”
Section: Discussionmentioning
confidence: 99%
“…All statistical data analyses were performed using the statistical software Prism (GraphPad, USA) and in SPSS statistical software (SPSS). All reported volumes were normalized for TIV, age, and sex using a linear regression model 8,23 . Group differences in demographic and clinical characteristics as well as normalized hypothalamic volumes were analyzed using independent two‐sample t test for continuous variables and χ 2 test for dichotomous variables.…”
Section: Methodsmentioning
confidence: 99%
“…IIH patients had to fulfill the standard diagnostic criteria according to Friedman et al 12 including a volumetric extension package, was used for the landmark-based volumetric analysis of the hypothalamus for IIH patients and controls in a three-step processing pipeline, as previously described. 13,14 First, a rigid brain normalization preserved the amount of hypothalamic volume. In a second step, spatial up-sampling into a study-specific grid ensured coronal slicing in a common space for all subjects by correcting for individual-based tilt of the head, followed by manual delineation of the left-and right-hemispheric hypothalamus.…”
Section: Methodsmentioning
confidence: 99%
“…Recent neuroimaging evidence complements early findings. A high-resolution MRI study of >360 participants found no significant difference in the hypothalamus volume of PD and non-PD individuals—thereby implying that the histopathologically detected involvement of the hypothalamus in PD is not observable as global hypothalamic atrophy, and further suggesting that the macrostructure of the hypothalamus remains rather stable throughout the disease course [ 135 ]. In line with the regulatory role of the hypothalamus in the autonomic nervous system, reduced hypothalamic functional connectivity with the thalamus and striatum was observed in PD patients with a higher burden of autonomic symptoms compared to those with a lower burden [ 136 ].…”
Section: Regions Of the Limbic Systemmentioning
confidence: 99%